Lithuanian dialect reserve. Social and geographical restrictions imposed on dialect mobility as reflected in direct attitudinal studies - Vaicekauskienė, Loreta; Sausverde, Ērika (Taikomoji kalbotyra, 2012)
The paper investigates a twofold attitude towards linguistic diversity in the Lithuanian-speaking community, where, on the one hand, the dialects are valorised as a national and ethnographic asset and, on the other hand, certain restrictions on their use are imposed because of association with a lower social value and negative stereotypes. Three direct attitudinal studies serve as an empirical basis for the research: a quantitative survey, qualitative interviews and an experiment with high-school students on stereotypical traits of the dialect speaker. When discussing future prospects of dialect change, the overt values of the speakers are compared with the findings of the speaker evaluation experiment that have revealed subconscious values of dialectal speech. The research has shown that compared to the Soviet times, the ideological climate regarding dialects has become more politically correct. Positive attitudes are most prominent at a declarative level and when regional identity and the speaker’s affiliation with a particular community have to be emphasised. Daily personal experiences, however, with the functionality of a dialect and evaluations of social and geographic mobility of dialect speakers, show a less favourable assessment of dialectal speech in comparison to the standard (non-dialectal) varieties. It is very much due to a frequent negative stereotyping of dialect speakers. The subconscious attitudes also reveal that the dialectal variability of speech has an arguably lower social meaning compared to the non-dialectal variability. The attitudes and practices of non-professional (lay) people may be claimed to reflect a double-faced standardization ideology of the Lithuanian language, which valorises dialects as an ecologic asset and at the same time limits their functioning by putting them in the reserve of “immobile” speakers.
Keywords: dialects; standard language; attitudes; social values; stereotypes; sociolinguistics